TOWARDS A RELIGIOUSLY HYBRID IDENTITY? The Changing Face of Javanese Islam (State Islamic University (UIN) of Sunan Ampel Surabaya, 2018)
This article seeks to revisit the discussion of Javanese Islam from an alternative point of view. It argues that the presentation of Javanese Islam in the previous studies is no longer adequate to accommodate the most current transformation of Javanese Islam. The identity of Javanese Islam can neither be seen from syncretic point of view nor normative perspective per se, since the identity of Javanese Islam has transformed itself into something different from the past. Becoming an abangan or santri in the post-Geertz era, represents the making of a religiously hybrid identity. In the context of Geertz, to become an abangan means he/she cannot become a santri at once. At that time, a pure and puritan abangan, was hardly a practicing Muslim, but nominal Muslim. Becoming a santri, on the other hand, had to be done by disentangling any type of identity in kejawen sense. Javanese Islam has to do with whatever-you-like mentality that forms a hybrid identity among the Javanese Muslims.